2020
DOI: 10.3390/su13010273
|View full text |Cite
|
Sign up to set email alerts
|

Building a Theoretical Framework for Corporate Sustainability

Abstract: Literature about sustainability and sustainable businesses has become a large field of study during the last years. This field is growing so fast that there are sub-areas or bodies of literature within the sustainability which scopes with clear boundaries between each other. This has caused the apparition of several methodologies and tools for turning traditional companies into sustainable business models. This paper aims to develop the descriptive stage of the theory building process through a careful review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 126 publications
0
24
0
Order By: Relevance
“…Researchers have claimed that the benefits associated with integrating sustainability into their business strategy and practices and improving their sustainability reporting include an increase in transparency, improved reputation and legitimacy, enhanced brand value, increased employee and customer loyalty, reduced costs, better business practices, improved firm performance and valuation, and competitive advantage generation (Herzig and Schaltegger 2006;Ioannou and Serafeim 2017;Sanchez-Planelles et al 2021). In fact, Brooks and Oikonomou (2018) and Xie et al (2019) have shown a strong correlation between the companies that provide sustainable reports and firm performance.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have claimed that the benefits associated with integrating sustainability into their business strategy and practices and improving their sustainability reporting include an increase in transparency, improved reputation and legitimacy, enhanced brand value, increased employee and customer loyalty, reduced costs, better business practices, improved firm performance and valuation, and competitive advantage generation (Herzig and Schaltegger 2006;Ioannou and Serafeim 2017;Sanchez-Planelles et al 2021). In fact, Brooks and Oikonomou (2018) and Xie et al (2019) have shown a strong correlation between the companies that provide sustainable reports and firm performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors focused on defining corporate sustainability in the realm of strong sustainability versus weak sustainability (see page 10 for definitions of weak and strong sustainability), highlighting how economic activity should be bounded within environmental limits [21,26,27] or on grounding corporate sustainability in the different organizational theoretical foundations such as stakeholder theory (corporate players must look beyond profit making goals and seek positive results for all stakeholders), institutional theory (corporate players must incorporate the latest practices to increase legitimacy and survival prospects), or resource-based theory (corporate players must use resources in a way that improves effectiveness of achieving superior competitive advantage) [10]. Other authors focused on defining sustainability through an in-depth semantic and historical analysis of the different terminologies related to sustainability [28][29][30][31] or through the identification of the key elements necessary for integrating it into corporate practices [3,4,15,32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, there has been a proliferation of studies around the subjects of sustainability, corporate sustainability, sustainable development, ESG, CSR and other associated terminologies [3]. Similarly, there has been a proliferation of initiatives to address the subject, both from a reporting and implementation standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…These stakeholders include people, governments, organizations, and industries, and their various purposes related to increasing wealth, quality of life, economy, and competitiveness. In fact, as Sanchez Planelles et al [51] state, sustainability practices, from a managerial point of view, have to respond to new challenges and stakeholder pressures. In addition, these authors observe different concepts of sustainability from a corporate sustainability perspective, including holistic sustainability, sustainable business models, sustainable methodologies, sustainable operations, and sustainability-oriented innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the introduction of sustainable practices and strategies can also reduce costs, improve the organizations' environmental, social and governance ratings or even lead them to build better performance and competitive advantage (as it can lead to more operational efficiency, or to offer more value to customers, resulting in higher number of customers, better customer engagement, or even more turnover). Moreover, the sustainable practices can help managers and practitioners develop and make better decisions; their analysis and study can help researchers to better understand the causal mechanisms that lead companies to embrace sustainability in a successful way [51].…”
Section: Introductionmentioning
confidence: 99%